Arterial dysfunction but maintained systemic blood pressure in cavin-1-deficient mice. - Karl Swärd (Public Library of Science (PLoS), 2014)
Caveolae are omega-shaped plasma membrane micro-domains that are abundant in cells of the vascular system. Formation of caveolae depends on caveolin-1 and cavin-1 and lack of either protein leads to loss of caveolae. Mice with caveolin-1 deficiency have dysfunctional blood vessels, but whether absence of cavin-1 similarly leads to vascular dysfunction is not known. Here we addressed this hypothesis using small mesenteric arteries from cavin-1-deficient mice. Cavin-1-reporter staining was intense in mesenteric arteries, brain arterioles and elsewhere in the vascular system, with positive staining of both endothelial and smooth muscle cells. Arterial expression of cavin-1, -2 and -3 was reduced in knockout (KO) arteries as was expression of caveolin-1, -2 and -3. Caveolae were absent in the endothelial and smooth muscle layers of small mesenteric arteries as determined by electron microscopy. Arginase, a negative regulator of nitric oxide production, was elevated in cavin-1 deficient arteries as was contraction in response to the α1-adrenergic agonist cirazoline. Detailed assessment of vascular dimensions revealed increased media thickness and reduced distensibility, arguing that enhanced contraction was due to increased muscle mass. Contrasting with increased α1-adrenergic contraction, myogenic tone was essentially absent and this appeared to be due in part to increased nitric oxide production. Vasomotion was less frequent in the knock-out vessels. In keeping with the opposing influences on arterial resistance of increased agonist-induced contractility and reduced myogenic tone, arterial blood pressure was unchanged in vivo. We conclude that deficiency of cavin-1 affects the function of small arteries, but that opposing influences on arterial resistance balance each other such that systemic blood pressure in unstressed mice is well maintained.